Seroprevalence of Brucellosis in Butchers, Veterinarians and Slaughterhouse Workers in Hamadan, Western Iran - Mamani, Mojgan (J Res Health Sci, 2018)
Background: Brucellosis is a zoonotic disease caused by Brucella species via infected domestic animals. In endemic areas, certain occupations such as veterinarians, butchers, and slaughterhouse workers are considered high risk regarding brucellosis. We evaluated the seroprevalence of brucellosis in high-risk occupations in Hamadan, West of Iran. Study design: a cross-sectional study. Methods: Overall, 218 participants from 2014 to 2015 were enrolled. A questionnaire including demographic data, length of employment, and using personal protective equipment was completed for each of them. Then, blood samples were taken and sent to Hamadan Health Center to be tested by Wright or standard tube agglutination (STA). In addition, samples with positive Wright test were examined by 2- mercaptoethanol (2ME) test. Then, seropositive participants were evaluated for clinical manifestations of brucellosis. All collected data were analyzed by SPSS ver. 16. Results: The mean age of the participants was 42.79±11.16 yr and all seropositive cases were male. Based on Wright ≥1/80 and 2ME ≥1/40, seroprevalence of brucellosis was 13.3% and 12.3%, respectively. The use of personal protective equipment was low among individuals with or without brucellosis. Myalgia, fatigue, back pain, joint pain, night sweats, fever, malaise, and headache were common symptoms in seropositive cases. Moreover, 20.6% of the seropositive participants were asymptomatic. Conclusions: Prevalence of brucellosis in these occupational groups and symptomatic disease in significant numbers of them was high, so periodic clinical examinations in these groups seems to be essential for brucellosis surveillance system.